Integral education a full-time: planning as a tool in management - Begnini, Sergio; Casagrande, Andreia (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The school manager is responsible for the administrative side of the school, however your main responsibility is to turn our attention to the subject of the existence of school learners. This study allows to deepen the understanding of organizational and environmental reality of the school, from a real case. The main goal is to present to the unit managers of integral education, tools that assist in the construction of strategic planning for better management of schools. The research is characterized by an exploratory, descriptive and conclusive character approach. For data collection structured questionnaires were used. Data were tabulated and analyzed using the SWOT matrix. After it was built the plan of actions, which show suggestions to put into practice. The research identified a need to qualify the managers in order to identify and overcome existing challenges and the need for strategic planning in everyday school life. We conclude that there is a great way to go and several barriers to overcome, especially in planning actions that will be implemented in the school environment.